The Influence of Social Media Utilization and Social Environment on Office Administration Students’ Entrepreneurial Interest - Siti Najwa Ananda Rianto (PENG: Jurnal Ekonomi dan Manajemen, 2026)
This study aims to examine the influence of social media utilization and social environment on students’ entrepreneurial interest. A quantitative approach with a correlational design was applied. Data were collected through an online questionnaire distributed to 100 active students of the Office Administration Education Study Program at Universitas Sebelas Maret from the 2021 and 2022 cohorts. The research instrument included three variables: social media utilization, social environment, and entrepreneurial interest. The results of multiple linear regression analysis showed that both social media utilization and social environment have a positive and significant influence, both partially and simultaneously, on students’ entrepreneurial interest. These findings support previous theories that entrepreneurial values can be strengthened through the integration of non-formal learning resources and social support. However, this study is limited to a single study program at one university. Therefore, future research with a broader respondent scope and a mixed-method approach is recommended to enrich the understanding of factors affecting entrepreneurial interest.